ВИЗНАЧЕННЯ ВПЛИВУ РОЗПОДІЛУ ЗОВНІШНЬОГО ЕЛЕКТРИЧНОГО ПОЛЯ ОПОРНО-СТРИЖНЕВОГО ІЗОЛЯТОРА НА ЙОГО СУХОРОЗРЯДНУ НАПРУГУ - Пальчиков , О.О. (Інститут електродинаміки НАН України, Київ, 2024)
A mathematical model has been developed for calculating the internal and external electric field of insulators based on the solution of the Laplace equation with respect to the phasor of the electric potential using the finite element method. The specified model has been used to calculate electric field intensity distributions in the surrounding air spaces of support-rod insulators С4-80-I, C4-80-II and also C4-80-IIСm (Chinese-made). It has been proposed to establish a relationship between the distribution of the electric field around the insulators and their test dry discharge voltage based on the average integral values of the modulus of the electric field intensity along the possible paths of the discharge, taking into account the sign of its tangential component. The average integral values of the electric field have been compared with the known experimental values of the air breakdown intensity between two rod electrodes, as well as in the electrode system of the rod and the grounded plane. It has been shown that the most probable path of development of the discharge for each of the considered insulators is the path closest to the minimum distance in the air between the cap and the flange, the discharge process is two-stage (firstly the section «cap-the rib nearest to the cap» is broken down), and the breakdown intensity of the air around the insulators corresponds to the breakdown intensity between two rod electrodes (the difference in values was 2,1...5,9%). References 10, tables 3, figures 3.